Cannabinoids and Their Role in Chronic Pain Treatment: Current Concepts and a Comprehensive Review - Islam Shehata; Ahmed Hashim; Ahmed Saad Elsaeidy; Anagha Nair; Ivan Urits; Omar Viswanath; Alan D. Kaye; Marian Habib (Health Psychology Research)
For decades, chronic pain was managed with an almost conventional approach of using a wide range of analgesic spectrum, surgical approaches and complex interventional pain techniques to modulate or even interrupt pain pathways. These different approaches carry many pharmacological hazards together with the lack of efficacy and safety of many interventional and surgical management techniques for chronic pain have mandated searching for other effective therapies including alternative treatments. Cannabinoids are naturally occurring substances that are derived from Cannabis sativa L. The usage of cannabinoids and their related synthetic chemical compounds has emerged as a choice in the management of different chronic pain conditions is being evaluated, however, the efficacy is still not consistently established. In the present investigation, therefore, we discuss the different aspects related to cannabinoids and their implications in the management of chronic pain conditions. This review will also discuss the safety profile of the cannabinoids together with the legal considerations that hinder their use in different countries.